Small plasmids harboring qnrB19: a model for plasmid evolution mediated by site-specific recombination at oriT and Xer sites - Tran, Tung (2012)
Fil: Tran, Tung. Center for Applied Biotechnology Studies, College of Natural Sciences and Mathematics, California State University Fullerton; Estados Unidos.